Antimicrobial activity of Indian Oregano (Coleus Aromaticus) against Diabetic wound pathogens - Kalesware A/P Muniandy
The antimicrobial activity of unsterilized and sterilized ethanolic extract of Coleus aromatic was evaluated by deploying disc diffusion, Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and time kill studies on Escherichia coli, Staphylococcus aureus, Klebsiella pneumonia, Pseudomonas aeruginosa and Proteus mirabilis. Zone of inhibition was 17.50 to 27.00 mm for unsterilized extract, 11.00 to 20.00 mm for heat sterilized extract, 6.00 to 12.00 mm for filter sterilized extract, 18.00 to 21.00 mm for ampicillin, 19.50 to 24.00 mm for chloramphenicol and 11.50 to 19.00 mm for streptomycin. MIC is 1.02 to 2.60 mg/ml for unsterilized extract, 2.60 to 5.21 mg/ml for heat sterilized 8.33 to 18.75mg/ml for filter sterilized extract and 0.02 mg/ml for chloramphenicol. MBC ranged from 2.60 to 8.33 mg/ml for unsterilized extract and from 0.03 to 0.04 mg/ml for chloramphenicol. Higher values were noted with heat (4.17 to 20.83 mg/ml). Time kill assay showed log reduction of more than 3 in 2 x MIC unsterilized extract on microorganisms tested. Greater log reduction was observed with heat sterilized extract compared to filter sterilized extract. The extract was also evaluated for its wound healing activity in induced diabetic mice. Excision wound model showed 76.6% of wound area reduction with higher rate of wound epithelialization in the presence of extract whereas the controls just exhibited 55.9% of wound area reduction. Dead space wound model showed increased granulation tissue and its histopathological investigation showed good proliferation of collagen tissue with satisfactory angiogenesis. This study showed the activity of C. aromaticus as adiabetic wound antimicrobial agent.